The PRAKTEK HIBAH SEBAGAI PENGGANTI WARISAN STUDY DIDESA PEMATANG PANJANG KECAMATAN LIMA PULUH PESISIR KABUPATEN BATU BARA: PRACTICE OF GRANT AS A REPLACEMENT OF HERITAGE STUDY IN PEMATANG PANJANG VILLAGE, FIFTY COASTAL DISTRICT, BATU BARA DISTRICT - Rizky Muhammad; Syaddan dintara Lubis (CV Rewang Rencang, 2024)
The issue at hand in this research focuses on how residents of Pematang Panjang village utilize grants as an alternative to inheritance, the factors influencing this practice, and the legal standing of grants under statutory provisions. This qualitative research aims for an in-depth understanding of the relevant phenomena and is categorized as empirical legal research utilizing a legal sociology approach. Methods such as interviews, observations, and document analysis are employed to deeply interpret the observed phenomena. In Islamic law, the transfer of property rights is termed a gift, defined as a voluntary transfer of goods without compensation between living individuals, as outlined in Article 171 letter (g) of the Compilation of Islamic Law (KHI). While gifts are typically voluntary, Article 211 indicates that gifts from parents to children can be viewed as part of an inheritance. However, Article 212 clarifies that gifts generally cannot be revoked, except for those given by parents to their children. In light of the observed phenomena, the practice of gifting as a substitute for inheritance in Pematang Panjang village may serve as a strategy to address various factors considered by heirs, and can be seen as an effort to promote fairness among them.